ANALYSIS OF INCLUSIVE ECONOMIC GROWTH INDEX AND INFLUENCING FACTORS (CASE STUDY OF REGENCIES/CITIES IN EAST JAVA PROVINCE) - Budiyanti, Fatwa; Hariyanti, Dini; Adriyana, Mona (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The purpose of this study is to identify the variables that would affect East Java Province's Regency / City inclusive economic development index between 2017 and 2021. This study employed a descriptive quantitative research design. The Fixed Effect Model (FEM) was chosen as the suitable model for this research's panel data regression analysis, which was conducted using the Eviews 13 analytic tool. The results showed that the variable level of employment opportunities, good condition roads, residents who have health insurance and decent drinking water sources had a significant effect on the inclusive economic growth index. Meanwhile, the gini ratio and poor population variables do not have a significant effect on the inclusive economic growth index. These findings indicate that the indicators in Pillar 2 of Income Equality and Poverty Reduction are not sufficient to influence the East Java Province's districts' and cities' inclusive economic growth index.Keywords: Inclusive Economic Growth Index, Employment Opportunities, Roads in Good Condition, Gini Ratio, Population with Health Insurance, Adequate Drinking Water Sources.